HEDONIC QUALITY OF KEMBANG GOYANG CAKE WITH VARIOUS LEVELS OF PANGASIUS MEAT FLOUR ADDITION - Ayuni Nasrunnisa; Junianto Junianto; Ayi Yustiati; Iis Rostini (Universitas Mataram, 2024)
This study aims to determine the optimal percentage of patin fish meat flour addition in making kembang goyang cake, in order to produce the most preferred product. The research was conducted from February to April 2024 at the Fishery Product Processing Technology Laboratory, Joint Building of Fisheries and Agriculture, Faculty of Fisheries and Marine Sciences, Padjadjaran University, and the Services Laboratory of UPTD Testing and Application of Fishery Product Quality (Pengujian dan Penerapan Mutu Produk Perikanan/ PPMPP) Cirebon, West Java Provincial Marine and Fisheries Office. The method used was an experimental method with variations in the levels of catfish meat flour in rocking flower cakes, consisting of four treatments (0%, 7.5%, 10%, and 12.5%), with 20 semi-trained panellists as replicates to determine the level of liking for the product. Observations were made through organoleptic tests. The results showed that the addition of 10% catfish meat flour resulted in the highest level of liking from the panellists, with a rating of 7 (preferred) for appearance, aroma, and texture, and 8 (preferred) for taste.